Heliox Allows for Lower Minute Volume Ventilation in an Animal Model of Ventilator-Induced Lung Injury - Beurskens, Charlotte J. (Public Library of Science, 2013)
BACKGROUND: Helium is a noble gas with a low density, allowing for lower driving pressures and increased carbon dioxide (CO(2)) diffusion. Since application of protective ventilation can be limited by the development of hypoxemia or acidosis, we hypothesized that therefore heliox facilitates ventilation in an animal model of ventilator–induced lung injury. METHODS: Sprague-Dawley rats (N=8 per group) were mechanically ventilated with heliox (50% oxygen; 50% helium). Controls received a standard gas mixture (50% oxygen; 50% air). VILI was induced by application of tidal volumes of 15 mL kg(-1); lung protective ventilated animals were ventilated with 6 mL kg(-1). Respiratory parameters were monitored with a pneumotach system. Respiratory rate was adjusted to maintain arterial pCO(2) within 4.5-5.5 kPa, according to hourly drawn arterial blood gases. After 4 hours, bronchoalveolar lavage fluid (BALF) was obtained. Data are mean (SD). RESULTS: VILI resulted in an increase in BALF protein compared to low tidal ventilation (629 (324) vs. 290 (181) μg mL(-1); p<0.05) and IL-6 levels (640 (8.7) vs. 206 (8.7) pg mL(-1); p<0.05), whereas cell counts did not differ between groups after this short course of mechanical ventilation. Ventilation with heliox resulted in a decrease in mean respiratory minute volume ventilation compared to control (123±0.6 vs. 146±8.9 mL min(-1), P<0.001), due to a decrease in respiratory rate (22 (0.4) vs. 25 (2.1) breaths per minute; p<0.05), while pCO(2) levels and tidal volumes remained unchanged, according to protocol. There was no effect of heliox on inspiratory pressure, while compliance was reduced. In this mild lung injury model, heliox did not exert anti-inflammatory effects. CONCLUSIONS: Heliox allowed for a reduction in respiratory rate and respiratory minute volume during VILI, while maintaining normal acid-base balance. Use of heliox may be a useful approach when protective tidal volume ventilation is limited by the development of severe acidosis.